2020
DOI: 10.3390/rs12111898
|View full text |Cite
|
Sign up to set email alerts
|

Data Reconstruction for Remotely Sensed Chlorophyll-a Concentration in the Ross Sea Using Ensemble-Based Machine Learning

Abstract: Polar regions are too harsh to be continuously observed using ocean color (OC) sensors because of various limitations due to low solar elevations, ice effects, peculiar phytoplankton photosynthetic parameters, optical complexity of seawater and persistence of clouds and fog. Therefore, the OC data undergo a quality-control process, eventually accompanied by considerable data loss. We attempted to reconstruct these missing values for chlorophyll-a concentration (CHL) data using a machine-learning technique base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…As a result, 17,192,761 pixels were used for model training, and 5,730,921 pixels were used for validation. Furthermore, the critical parameters determining ultimate model performance, number of trees, and number of features were set to 60 and 3, consistent with those in [21]. As such, the R-squared (R 2 ), root mean square error (RMSE), and mean absolute error (MAE) for the training set were 0.99, 0.02 mg m -3 , and 0.01, respectively (Figure 1).…”
Section: Filling Gaps On Chl-a Datamentioning
confidence: 84%
See 2 more Smart Citations
“…As a result, 17,192,761 pixels were used for model training, and 5,730,921 pixels were used for validation. Furthermore, the critical parameters determining ultimate model performance, number of trees, and number of features were set to 60 and 3, consistent with those in [21]. As such, the R-squared (R 2 ), root mean square error (RMSE), and mean absolute error (MAE) for the training set were 0.99, 0.02 mg m -3 , and 0.01, respectively (Figure 1).…”
Section: Filling Gaps On Chl-a Datamentioning
confidence: 84%
“…We used a machine learning technique to fill the cloud-induced gaps in ocean color, which allows for a more accurate interpretation of phytoplankton biomass in time and space. At high latitudes, ocean color products such as Chl-a contain massive missing data due to various causes, such as the presence of clouds and sea ice [21]. If the spatial and temporal mean is constructed with missing data, the accuracy may be significantly affected [22].…”
Section: Filling Gaps On Chl-a Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the bias caused by the different measurement depth was corrected for the satellite-derived SSTs (refer to 2.2). RF has been widely used to examine the regression problems of ocean parameters in recent years [26][27][28][30][31][32]56]. RF is a nonparametric ensemble approach that composes a multitude of bootstrapped regression trees [57][58][59][60][61].…”
Section: Variable Type Variablementioning
confidence: 99%
“…Park et al (2019) also found that the CHL reconstructed for multiple variables through the RF model more accurately simulated spatial patterns and CHL values when compared with other techniques. In addition, Park et al (2020) qualitatively and quantitatively studied the effects of various factors on CHL through RF.…”
mentioning
confidence: 99%